Perbandingan Efektivitas Audio Advertising Spotify dan Social Media Advertising sebagai Media Komunikasi Pemasaran Digital - Dharmawan , Dito Dzaki; Rianto, Puji (Program Studi Ilmu Komunikasi UII, 2024)
This research aims to evaluate the effectiveness of Spotify Audio Advertising and Social Media Advertising as digital marketing communication media and to identify the differences in effectiveness between the two digital marketing communication media. This research was conducted at the Faculty of Psychology and Social and Cultural Sciences, Universitas Islam Indonesia. A total of 92 respondents were purposively selected. Data analysis was performed using the EPIC Model, focusing on data description and independent two-sample t-tests to examine the difference in effectiveness between the two digital marketing media. The results indicate that the respondents considered Spotify Audio Advertising fairly effective, while Social Media Advertising was regarded as effective. The independent t-test between the two media revealed a significance value (2-tailed) of 0.000, smaller than the α value set at 0.05. This indicates that the difference in the average effectiveness between the two digital marketing media is significant.